PENGARUH MODEL PEMBELAJARAN GAME-ORIENTED PROBLEM EXPLORATION (GOPE) BERBANTUAN MEDIA WORDWALL TERHADAP KETERAMPILAN MEMAHAMI TEKS NEGOSIASI PADA SISWA KELAS X SMAN 7 PADANG - Affanza, Anggia; Indriyani, Vivi; Abdurrahman; Syafrina, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motiated by students low ability in understanding negotiation texts due to conventional and less interactive learning methods. This study aims to dtemine the effect of the Game-Oriented Problem Exploration (GOPE) learning model assisted by Wordwall media on students’ ability to understand negotiation texts in grade X of SMAN 7 Padang. This study employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The sample consisted of an experimental class and a control class selected through purposive sampling. The research instrument was an objective test administered as pretest and posttest. The results showed that the average score of the experimental class increased from 70.75 to 86.53, while the control class increased from 72.87 to 82.16. The hypothesis testing indicated that the t-value (3.07) was higher than the t-table value (1.99) at a significance level of 0.05. Thus, it can be concluded that the GOPE learning model assisted by Wordwall media has a significant effect on students’ ability to understand negotiation texts.